EXPRESSION PATTERNS OF THE HUMAN RIBOSOMAL PROTEIN GENES eL14 AND uS19 IN COLON CANCER IS DEPENDENT ON THE TYPE AND STAGE OF THE CANCER CELL - SIM, EDMUND UI-HANG; MUTSAMY , SELVAMALAR; TEH, ZY-YING (Malaysian Applied Biology, 2020)
Although the association of some ribosomal protein genes with colorectal cancer is widely known, the detailed mechanisms and complete list of associated genes is lacking. More importantly, the behaviours of these genes in different types and stages of the cancer are poorly understood. Herein we report the study of two ribosomal protein genes in cell lines derived from different sites and stages of colon cancer. Specifically, we analysed the expression pattern of eL14 and uS19 in HCT116 and SW480 cell lines. These two genes, although associated with a wide variety of cancer types, are poorly or have not been studied in colorectal cancer. Semi-quantitative reverse transcription – polymerase chain reaction (RT-PCR) approach was used, together with Students’ t-test validation. We found a significantly (p < 0.05) differential eL14 and uS19 expression patterns between HCT116 and SW480 cell lines. Our findings suggest that eL14 and uS19 have higher activity in a poorly differentiated cell line derived from advanced (metastatic) stage (Duke’s Stage D) colorectal carcinoma tissues compared to the moderately differentiated cell line derived from a mid-stage (Duke’s Stage B) colorectal adenocarcinoma tumour. This will have important implications for both ribosomal protein genes as type and stage specific biomarkers for colon cancer